In Vivo (1)H MR Spectroscopy of Human Head and Neck Lymph Node Metastasis and Comparison with Oxygen Tension Measurements - Star-Lack, Josh M. (AJNR Am J Neuroradiol, 2000)
BACKGROUND AND PURPOSE: Current diagnostic methods for head and neck metastasis are limited for monitoring recurrence and assessing oxygenation. (1)H MR spectroscopy ((1)H MRS) provides a noninvasive means of determining the chemical composition of tissue and thus has a unique potential as a method for localizing and characterizing cancer. The purposes of this investigation were to measure (1)H spectral intensities of total choline (Cho), creatine (Cr), and lactate (Lac) in vivo in human lymph node metastases of head and neck cancer for comparison with normal muscle tissue and to examine relationships between metabolite signal intensities and tissue oxygenation status. METHODS: Volume-localized Lac-edited MRS at 1.5 T was performed in vivo on the lymph node metastases of 14 patients whose conditions were untreated and who had primary occurrences of squamous cell carcinoma. MRS measurements were acquired also from the neck muscle tissue of six healthy volunteers and a subset of the patients. Peak areas of Cho, Cr, and Lac were calculated. Tissue oxygenation (pO(2)) within the abnormal lymph nodes was measured independently using an Eppendorf polarographic oxygen electrode. RESULTS: Cho:Cr ratios were significantly higher in the nodes than in muscle tissue (node Cho:Cr = 2.9 ± 1.6, muscle Cho:Cr = 0.55 ± 0.21, P = .0006). Lac was significantly higher in cancer tissue than in muscle (P = .01) and, in the nodes, showed a moderately negative correlation with median pO(2) (r = −.76) over a range of approximately 0 to 30 mm Hg. Nodes with oxygenation values less than 10 mm Hg had approximately twice the Lac signal intensity as did nodes with oxygenation values greater than 10 mm Hg (P = .01). Cho signal intensity was not well correlated with pO(2) (r = −.46) but seemed to decrease at higher oxygenation levels (>20 mm Hg). CONCLUSION: (1)H MRS may be useful for differentiating metastatic head and neck cancer from normal muscular tissue and may allow for the possibility of assessing oxygenation. Potential clinical applications include the staging and monitoring of treatment.